Factors affecting cell viability and the yield of adipose-derived stromal vascular fraction. Issue 4 (1st August 2022) - Karadag Sari, E. Cigdem; Ovali, Ercument
Abstract: The stromal vascular fraction (SVF) is isolated from adipose tissue and has tremendous regenerative potential for proliferation and differentiation. This study aimed to investigate the factors affecting the cell yield and viability of the SVF to improve the outcomes of its clinical applications and enhance its clinical usage. We performed a retrospective analysis with 121 patients who underwent liposuction to harvest adipose-derived SVF. We recorded patient demographic and clinical characteristics, including age, sex, body mass index (BMI), blood type, medical comorbidities, and smoking and alcohol consumption. As for operative variables, we noted the amount of lipoaspirate and the donor areas, including the lower and entire abdomen. The viability and the cell count of SVF were documented. Sex was a statistically significant factor for viability rate ( p  < 0.015) and cell count ( p  < 0.009). Men had higher viability, while women had higher cell counts. We found a statistically significant difference in the presence of hypertension ( p  = 0.024) and alcohol consumption ( p  = 0.024). There was a statistically significant relationship between cell count and age ( p  < 0.001), BMI ( p  = 0.006), and amount of lipoaspirate ( p  < 0.001). Sex had significant associations with cell count and viability, while age, BMI, and lipoaspirate amount were significantly associated with cell count. Hypertension and alcohol consumption significantly affected cell count, which is the first such report of this association. Surgeons could apply this knowledge to patient selection for optimal treatment outcomes. Additionally, understanding these factors can help manage patient expectations.